Electronic Media as the Tool for Preserving Ancient Language: Web Resource “Khalmg Keln” (The Kalmyk Language) - Victoria Vasiljevna Kukanova; Valentin Ivanovich Rassadin; Svetlana Menkenovna Trofimova; Badma Katinovich Salaev (International Review of Management and Marketing, 2015)
According to UNESCO data, the Kalmyk language has faced a real threat of dying-out and is currently a declining language. In this respect the creation of e-textbooks becomes a burning issue. They would serve as educational information resources, which combines modern methods and play the role of encyclopedias. This article aims at describing the structure, basic problems and development process of this online educational information resource. The main objective of this e-textbook is to simplify learning of the Kalmyk language, develop the oral speech in the Kalmyk language and forward the Kalmyk culture. The educational information resource presents experience of those people who have been teaching children starting from kindergartens the Kalmyk language and the Kalmyk literature while taking into consideration their ethnic peculiarities. This article is mainly concerned with describing the structure, basic problems and development process of this online educational information resource, and also dwells upon spelling rules of the Kalmyk language, methods of teaching the Kalmyk language as a foreign one and introduction of information technologies to the sphere of teaching.